Merger Control in Ireland: Too Many Unnecessary Merger Notifications? - GORECKI, PAUL K. (ESRI)
The market for corporate control plays an important role in ensuring that assets are deployed in an efficient and effective manner. However, on occasion, mergers might lead to a reduction in competition and a consequent rise in prices and/or other anticompetitive effects. The Competition Act 2002 provides that all mergers that meet certain financial thresholds must be notified to the Competition Authority in order that they are subject to a competitive effects assessment. However, there are concerns that the notification thresholds result in many mergers with little or no nexus to Ireland being notified. While it is the case that the vast majority of merger notifications do not raise competition concerns, Ireland is not out of line with other jurisdictions which have mandatory notification thresholds such as the EU and the US. Nevertheless, that should not lead to complacency. The paper quantifies the impact of reforms made in 2006 and 2007 by the Competition Authority and the Minister of Enterprise, Trade and Employment to the merger notification thresholds. The evidence suggests that these tighter better specified thresholds led to a reduction of at least 40-50 per cent in the number of merger notifications. However, more could be done, albeit probably to a lesser extent than the earlier reforms. Applying the International Competition Network's Recommended Practices for Merger Notification Procedures, a series of proposals are made in the paper for revising the merger notification thresholds to better select mergers with a nexus to Ireland. Such moves should facilitate a more effective and efficient market for merger control by reducing transaction costs involved in the merger process as well as allowing Competition Authority resources to be deployed elsewhere, a not inconsiderable advantage in a period of austerity.
PUBLISHED
Keywords: employment; MERGERS; Ireland; competition; competition act; US; cost